Care pathway process proposal and rationale for the assessment and management of firesetting in the inpatient setting. (26th January 2015) - Hillier, Bradley; Cherukuru, Srinivasarao; Sethi, Faisil
Abstract: Firesetting is traditionally a forensic problem which is nevertheless a frequent co-morbidity within mental health settings. The associations between mental health and firesetting are diverse and poorly understood, and with forensic services under increasing pressure, non-forensic settings may be increasingly expected to manage such presentations. With this in mind, and in the absence of a specific risk assessment tool, we propose a care pathway and rationale for its use in the assessment and management of individuals with firesetting behaviours as part of their presentation.